Marketing Performance: Unpacking Market Orientation Mediated Innovation Capability and Sustainable Competitive Advantage of Small and Medium Enterprises Food - Muhammad Fahmi; Muhammad Andi Prayogi; Muhammad Taufik Lesmana; Maharani Citra Kencana; Syahita Syahita (Indonesian Journal of Sustainability Accounting and Management, 2024)
This research examines how market orientation influences marketing performance by mediating innovation capability and Sustainability Competitive Advantage. This research uses a quantitative approach to collect data and analyze the relationships between variables. The research sample consisted of 348 food-producing SME business actors in North Sumatra. Data analysis in this research uses Structural Equation Modeling (SEM) with the Partial Least Squares (PLS-SEM) method. The research results show that there is a direct influence of Innovation capability and sustainable Competitive Advantage on marketing performance. There is an influence of Market Orientation on Innovation Capability and Sustainable Competitive Advantage, but there is no influence of Market Orientation on Marketing performance. Then, innovation capability and sustainable competitive advantage have a mediating role in market orientation and marketing performance. This research provides a new contribution to understanding the factors that influence the marketing performance of SMEs. Combining market orientation, innovation capability and sustainable competitive advantage as mediation is an approach that has yet to be widely explored in previous literature. Practical implications for SME owners, business organizations, and government policies: Improving market orientation, innovation capabilities, and sustainability can help SMEs improve marketing performance, contributing to sustainable economic growth.